From Soft to Hard Law and Interpretation: the Case of the OECD Guidelines for Multinational Enterprises and the Role of the National Contact Points - Maria Chiara Malaguti (Oslo Law Review)
The Norwegian Transparency Act imposes on businesses to respect human rights and ensure decent working conditions, as well as a duty to carry out due diligence in accordance with the OECD Guidelines for Multinational Enterprises. Countries adhering to the Guidelines are required to set up National Contact Points (NCPs), which are tasked with furthering the effectiveness of the Guidelines and to offer a grievance mechanism to resolve cases relating to non-observance of the Guidelines. Since the fundamental human rights and decent working conditions referred to by the Transparency Act are expansive concepts directly deriving from international standards, the evolution of the Guidelines through the concrete interpretation by the NCPs plays a role in the implementation of the Act itself. This contribution examines the implementation by NCPs of some of the core elements of the Guidelines, including which are the relevant stakeholders whose interests are protected in concrete cases, the responsibility of companies for their direct and indirect suppliers, and the coverage of the Guidelines also of minority shareholders and financial investors, which have no direct control of the actions of a business entity. The NCPsʼ implementation of international standards might thus have an impact on the general categories of domestic legislation and will thus affect—even if indirectly—the general understanding of respect for sustainability standards in domestic systems.